Diminishing benefit of smoking cessation medications during the first year: a meta‐analysis of randomized controlled trials. (29th January 2018) - Rosen, Laura J.; Galili, Tal; Kott, Jeffrey; Goodman, Mark; Freedman, Laurence S.
Abstract: Background and aims: Although smoking cessation medications have shown effectiveness in increasing abstinence in randomized controlled trials (RCTs), it is unclear to what extent benefits persist over time. This paper assesses whether the benefits of smoking cessation medications decline over the first year. Methods: We selected studies from three systematic reviews published by the Cochrane Collaboration. RCTs of first‐line smoking cessation medications, with 6‐ and 12‐month follow‐up, were eligible for inclusion. Meta‐analysis was used to synthesize information on sustained abstinence (SA) at 6 versus 12 months and 3 versus 6 months, using the risk difference (RD) ('net benefit') between intervention and control group quit rates, the relative risk (RR) and the odds ratio (OR). Results: Sixty‐one studies (27 647 participants) were included. Fewer than 40% of intervention group participants were sustained abstinent at 3 months (bupropion: 37.1%; nicotine replacement therapy (NRT): 34.8%; varenicline: 39.3%); approximately a quarter were sustained abstinent at 6 months (bupropion: 25.9%; NRT: 26.6%; varenicline: 25.4%), and approximately a fifth were sustained abstinent at 12 months (bupropion: 19.9%; NRT: 19.8%%; varenicline: 18.7%). There was only a small decline in RR (3 months: 1.95 [95% confidence interval (CI) = 1.74–2.18, P < 0.0001]; 6 months: 1.87 (95% CI = 1.67–2.08 P < 0.0001); 12 months: 1.75 (95% CI = 1.56–1.95, P < 0.0001) between intervention and control groups over time, but a substantial decline in net benefit [3 months: RD = 17.3% (14.5–20.1%); 6 months: RD = 11.8% (10.0–13.7%); 12 months: RD = 8.2% (6.8–9.6%)]. The decline in net benefit was statistically significant between 3 and 6 [RD = 4.95% (95% CI = 3.49–6.41%), P < 0.0001] and 6 and 12 months [RD = 3.00% (95% CI = 2.36%–3.64%), P < 0.0001)] for medications combined and individual medications. Conclusions: The proportion of smokers who use smoking cessation medications who benefit from doing so decreases during the course of the first year, but a net benefit still remains at 12 months.